CDK12 Promotes Cervical Cancer Progression through Enhancing Macrophage Infiltration - Bikang Yang; Jing Chen; Yincheng Teng (Journal of Immunology Research)
Cervical cancer (CC) is a commonly diagnosed and primary consideration of cancer patient death in female reproductive system malignancy. Cyclin-dependent kinase 12 (CDK12), as a transcription-associated CDK, plays important roles in tumor-promoting behaviors, whereas the underlying mechanisms of CDK12 in CC progression are still obscure. In this report, we investigated the role of CDK12 in cervical cancer. The current study identified CDK12 mRNA and protein expression remarkably upregulated in CC patients. Upregulated CDK12 was closely associated with CC progression and poor prognosis. In vitro and in vivo functional experiments showed that knockdown of CDK12 inhibited cancer cell proliferation and colony formation and promoted apoptosis. Further investigations demonstrated that CDK12 regulated the immune microenvironment to facilitate the progression of CC cells by promoting macrophage infiltration. Meanwhile, we first demonstrated that nuclear import of CDK12 is mediated by TNPO1 and might be a new therapeutic target in oncology. Collectively, this study pointed out the potential of CDK12 to serve as a novel therapeutic target in restricting CC proliferation and cell cycle process through promoting macrophage infiltration.